EVALUASI KESESUAIAN LAHAN TANAMAN SORGUM (Shorgum bicolor) DI KECAMATAN BILAH BARAT, KABUPATEN LABUHANBATU - Fitra Syawal Harahap; Rahmaniah Rahmaniah; Simon Haholongan Sidabuke; Muhammad Zuhirsyan (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Sorghum has great potential to be cultivated and developed commercially because it has wide adaptability, high productivity, is resistant to plant pests and is more resistant to marginal conditions. Land evaluation is useful as a basis for sector development in an area that is useful for reorganizing the existing land use to assist in making land use planning decisions. This study that was aimed to evaluate land suitability for sorghum was conducted descriptively using the survey method. The sampling method used was based on a land map unit with a free grid system. The land evaluation was carried out by matching and comparing land characteristics with land suitability class criteria to obtain land suitability classes for sorghum plants in Bilah Barat District, Labuhanbatu Regency. There were six soil sample points collected at a depth of 0-60 cm to determine the value of soil characteristics. The results showed that the cultivated sorghum in Bilah Barat District, Labuhanbatu Regency of 12,829 ha which has the actual land suitability class for sorghum is Nwa with the potential land suitability class is S2tcwa.Â